Imprisoned minds: lost boys, trapped men, and solutions from within the prison - Maloney, Erik S. (Critical issues in crime and society, 2025)
"Imprisoned Minds" tells the stories of men in prison that few people ever hear: gripping, first-person narratives of the unimaginable childhood trauma and neglect that set them on a pathway for prison or death. Erik S. Maloney interviews these prisoners with candor and savviness; he can do this because he is in prison alongside them - incarcerated for life at the age of twenty-one. With correctional scholar Kevin A. Wright, he presents a unique and informed perspective that blends lived experience with academic knowledge, reminding us of the humanity of the nearly two million people behind bars in the United States and encouraging solutions from within to break the cycle of intergenerational incarceration.